2016
DOI: 10.1007/s10549-016-3893-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intratumoural heterogeneity on the assessment of Ki67 expression in breast cancer

Abstract: In breast cancer (BC), the prognostic value of Ki67 expression is well-documented.Intratumoural heterogeneity (ITH) of Ki67 expression is amongst the several technical issues behind the lag of its inclusion into BC prognostic work-up. The immunohistochemical (IHC) expression of anti-Ki67 antibody (MIB1 clone) was assessed in four full-face (FF) sections from different primary tumour quadrants and their matched axillary nodal (LN) metastases in a series of 55 BC. Assessment was made using the highest expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…Moreover, metastatic tumor cells were highly proliferative and associated with Ki-67 levels in the highest expression hot spots in primary tumors. This may reflect the temporal heterogeneity through clonal expansion of the primary tumor growth fraction with metastatic potential ( 92 ).…”
Section: Intratumor Heterogeneitymentioning
confidence: 99%
“…Moreover, metastatic tumor cells were highly proliferative and associated with Ki-67 levels in the highest expression hot spots in primary tumors. This may reflect the temporal heterogeneity through clonal expansion of the primary tumor growth fraction with metastatic potential ( 92 ).…”
Section: Intratumor Heterogeneitymentioning
confidence: 99%
“…7B). A number of studies have confirmed that Ki67 protein expression is a strong indicator of patient outcome [52]; therefore, we determined the Ki67 expression in each group. Tumor tissues were collected, and Ki67 expression was assessed using immunohistochemistry (IHC).…”
Section: Combination Treatment Suppresses Tumor Growth In Xenograft Mmentioning
confidence: 99%
“…Recently, we evaluated the expression of Ki67 in multiple areas from a subset of primary invasive BC and in the corresponding lymph node metastasis [96], and found a high degree of variation in the expression across the areas on the slide from the same tumour block as well as between slides from different tumour blocks. Interestingly, the highest scores of Ki67 in primary tumours coincided with those in the nodal metastatic deposits (Fig.…”
Section: Heterogeneity and The Efficacy Of Targeted Therapymentioning
confidence: 99%